Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.36076/ppj.2021.24.e565
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nociceptive Effects of Dexmedetomidine Infusion Plus Modified Intercostal Nerve Block During Single-port Thoracoscopic Lobectomy: A Double-blind, Randomized Controlled Trial

Abstract: BACKGROUND: Multimodal general anesthesia based on modified intercostal nerve block (MINB) has been found as a novel method to achieve an intraoperative opioid-sparing effect. However, there is little information about the effective method to inhibit visceral nociceptive stress during single-port thoracoscopic surgery. OBJECTIVE: To investigate whether a low-dose dexmedetomidine infusion followed by MINB might be an alternative method to blunt visceral stress effectively. STUDY DESIGN: Double-blind, randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“… 16 , 17 Thus, a clinical trial demonstrated that DEX ameliorated visceral pain after abdominal surgery in patients via a dose-dependent inhibitory on C-fibers and Aα-fibers. 18 Also, our preliminary study 3 showed an intra-operative opioid-sparing effect extending 48 h after surgery after MINB and intra-operative DEX infusion might be an alternative method to blunt visceral stress effectively in patients undergoing thoracoscopic lobectomy. This current study focused on the postoperative opioid-sparing effect and further demonstrated the feasibility of postoperative opioid-free analgesia.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“… 16 , 17 Thus, a clinical trial demonstrated that DEX ameliorated visceral pain after abdominal surgery in patients via a dose-dependent inhibitory on C-fibers and Aα-fibers. 18 Also, our preliminary study 3 showed an intra-operative opioid-sparing effect extending 48 h after surgery after MINB and intra-operative DEX infusion might be an alternative method to blunt visceral stress effectively in patients undergoing thoracoscopic lobectomy. This current study focused on the postoperative opioid-sparing effect and further demonstrated the feasibility of postoperative opioid-free analgesia.…”
Section: Discussionmentioning
confidence: 91%
“…Near the incision site where a chest drainage tube was inserted, the ultrasound transducer (S-Nerve; SonoSite Iberica S.L., Madrid, Spain) was placed perpendicular to the long axis of the upper rib (posterior axillary line level). As the previous protocol by our study, 3 the 21G needle was inserted which targeted the lateral border of the upper rib in a caudal-to-cephalic direction along the long axis of the transducer. Then 5 mL of 0.35% ropivacaine combined with 0.025% dexamethasone was injected when the needle reached this special landmark, which facilitated the drug’s diffusion up, down, and back, between the anterior serratus muscle and the coastal space ( S. Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation